1966
DOI: 10.2135/cropsci1966.0011183x000600050011x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Selection of Productive S1 Inbred Lines of Corn (Zea mays L.)1

Abstract: Two recurrent selection series, originating from the same 153 S1 lines, were carried through two complete cycles. Selection was based on testcross yield in one series and on S1 progeny yield in the other. The mean S1 yield increased 31.4% with 2 cycles of selection for S1 yield and 17.9% with 2 cycles of selection for testcross yield. The more productive S1 lines tended to produce the more productive crosses, but the correlation between S1 and testcross yields decreased with each cycle of selection. Four S1 li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
13

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 0 publications
1
8
0
13
Order By: Relevance
“…Wright (1977) found that Si testing compared favourably with half-sib and testcrossing for a range of models which included ambi-directional dominance and epistasis, and the present study has confirmed that this method has a robustness in the face of differing genetic conditions which lead to its general superiority over other progeny testing methods for typical trial designs. The considerable weight of experimental evidence in maize also indicates a general superiority of this method (Genter and Alexander, 1966;Genter, 1973;Carangal et al 1971;Lonnquist, 1968).…”
Section: Discussiormentioning
confidence: 99%
“…Wright (1977) found that Si testing compared favourably with half-sib and testcrossing for a range of models which included ambi-directional dominance and epistasis, and the present study has confirmed that this method has a robustness in the face of differing genetic conditions which lead to its general superiority over other progeny testing methods for typical trial designs. The considerable weight of experimental evidence in maize also indicates a general superiority of this method (Genter and Alexander, 1966;Genter, 1973;Carangal et al 1971;Lonnquist, 1968).…”
Section: Discussiormentioning
confidence: 99%
“…Diante da existência de variabilidade entre progênies oriundas de autofecundação, torna-se possível selecionar genótipos com menor depressão endogâmica (Genter & Alexander, 1966) ou com características desejáveis, conforme procedimento adotado na seleção do cultivar Mott (Sollenberger & Jones Jr., 1989).…”
Section: Resultsunclassified
“…Center and Alexander (1962) compared the performance of SI progenies and testcrosses and concluded that if heterosis was a result of additive effects from dominant genes, progeny performance of early generation inbred lines should evaluate their general combining ability better than testcrosses. Center and Alexander (1966), working with Corn Belt Southern Synthetic, reported an increase of 31.4% and 17.9% in the mean yield of SI lines after two cycles of selection for SI families and testcrosses, respectively. They also found that the more productive Si lines tended to produce the more productive crosses, but that relationship decreased with each cycle of selection.…”
Section: Inbred Family Selectionmentioning
confidence: 99%